THE “GALLIC MORBIDITY” (SYPHILIS) DURING THE LATE COLONIAL PERIOD: THE TENSION BETWEEN THE LEGAL-RELIGIOUS MORAL AND HYGIENIST RATIONALITY. THE CASE OF THE PETRONA SLAVE. SANTIAGO, CHILE 1806-1808. - Celis Valderrama, Nicolás (Revista de Historia Social y de las Mentalidades, 2024)
The present article aims to show the tension  between the legal-religious moral and the  rational hygienist paradigm shown through the  legal case followed by Mr. Nicolás Ambrosi  Churale with Mr. Francisco Ramón Vicuña,  about: ‘nullity of the sale of a sick slave from  Gallic. Sale of the Petrona slave, since August  29th, 1806, until August 26th, 1808”. To  accomplish this, we will use the encounter of  two paradigms, one assumed by the litigants and  their representatives (legal-religious moral), and  the other one assumed by doctors and surgeons  (hygienist rational) summoned during trial. This  article does not intend to lose track of the traces  kept by the file itself, being this the column  of this text, and assuming that the intended  approach to use is oriented towards the impact  of the disease, beyond the litigation of the sale  nullity.
Keywords: Gallic morbidity; Hygienist rationality; Legal-religious moral; Late colonial; Chile